High temperature corrosion of stainless steels : an Alain Galerie festschrift : selected, peer reviewed papers from the Alain Galerie Symposium on High Temperature Corrosion, 9 July, 2018, Bangkok, Thailand - Chandra-ambhorn, Somrerk; Wouters, Yves; Harnnarongchai, Wanlop (Diffusion and defect data. Solid state phenomena ;, 2020)
This book provides the basic concepts and the recent research - in thermodynamic, kinetic and mechanical aspects - of the high temperature corrosion of stainless steels. It also includes the reviews of the effects of alloying elements and water vapour on stainless steel oxidation, as well as the development of stainless steel interconnects for solid oxide fuel cells. This festschrift is published in honour of Professor Alain Galerie as an outgrowth of the Alain Galerie Symposium on High Temperature Corrosion held at King Mongkut's University of Technology North Bangkok, Thailand, on 9 July 2018. Stainless Steel, High Temperature Corrosion, Alloying Elements, Thermal Oxide, Oxidation Kinetics, Thermodynamic Analysis Materials Science, Manufacturing.